Mini‐invasive approach for removal of iliopsoas migrating grass awns with an atraumatic wound retractor. (11th September 2019) - Moretti, G.; Birettoni, F.; Caivano, D.; Nannarone, S.; Crovace, A.; Porciello, F.; Bufalari, A.
Abstract : This case series describes a novel mini coeliotomy approach using a radial, atraumatic self‐retaining retractor for the retrieval of migrant plant foreign bodies from the iliopsoas muscles of six male dogs under intra‐operative ultrasonographic guidance. Four dogs had a history of pulmonary disease potentially compatible with inhalation of a foreign body approximately 2–4 months before presentation. Under ultrasonographic guidance, the grass awns were identified in the iliopsoas muscle and were completely removed. In this case series, the annular ring device provided an excellent view of the surgical field for intra‐abdominal manipulations. Patient follow‐up at 15 days and 6 to 12 months after surgery indicated a full recovery, and no grass awn fragment residues were identified.